Biotechnology in assisted human reproduction (Portuguese Journal of Family Medicine and General Practice, 2005)
The knowledge in the field of human reproduction has shown great development over the past three decades, resulting in the introduction of new technologies available to reproductive medicine and research in reproductive biology.The aim of this study was to address, in a systematic and synthetic technology today that can be used in assisted human reproduction.
Keywords: Assisted Reproduction; Infertility; Sterility